Information Literacy Against Interest in Making Online Loans With Ease of Use as a Moderating Variable for Muslim Entrepreneurs in Indonesia - Prajogo, Uke (Program Studi Ekonomi Islam Fakultas Ekonomi dan Bisnis Islam Institut Agama Islam Syarifuddin Lumajang, 2023)
This study aims to analyze and prove the effect of information literacy variables on interest in making online loans with perceived ease of use as a moderating variable. The results of this study are expected to be useful and contribute to technology-based financial services, especially in peer-to-peer lending in order to provide safe and good quality services for the community. The object of this research is Indonesia a students who are members of ABM Preneur. The data used in this study is primary data, which was obtained through the distribution of online questionnaires. The sampling method was stratified purposive random sampling. The results showed that information literacy had a negative and partially insignificant effect